2012
DOI: 10.1007/s10578-012-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Continuity of Child Mental Health Problems from Preschool to Primary School: Results of a Four-Year Longitudinal Study

Abstract: In a four-year longitudinal study, changes in and continuity of behavioral and emotional problems were examined in 814 subjects from kindergarten to primary school. Mental health problems were assessed by means of the Child Behavior Checklist (CBCL). The distribution of the CBCL broadband groups revealed a high level of continuity of internalizing symptoms over the four-year period and a shift from externalizing symptoms at baseline towards a combination of internalizing and externalizing symptoms at follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 29 publications
4
35
1
2
Order By: Relevance
“…They showed that approximately half of all lifetime mental disorders begin during adolescence. Research on preschool mental health indicates that MHPs show substantial stability and are strongly predictive of mental disorders in adolescence [8, 11, 12]. Within a population-based cohort Basten et al [13] examined the stability of internalizing and externalizing problems from children aged 1.5–6 years.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that approximately half of all lifetime mental disorders begin during adolescence. Research on preschool mental health indicates that MHPs show substantial stability and are strongly predictive of mental disorders in adolescence [8, 11, 12]. Within a population-based cohort Basten et al [13] examined the stability of internalizing and externalizing problems from children aged 1.5–6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from high-income countries have shown that poor language skills in early grades may lead to frustration, avoidance and a negative attitude towards school and literacy. 46 Oral language development, along with the ability to hear and record sounds, has also been demonstrated as a strong predictor of writing development, which in turn is important for success at school in general. With evidence from high-income countries suggesting that language and literacy skills are instrumental to success in the first years of, future research should assess if enhanced language development due to MISC results in better preparing HEU children for school.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies of community samples or birth cohorts report that few young children have high internalising (eg, anxiety, depression) and/or externalising behaviours (eg, oppositional behaviour) at any assessment period, and that very few continue these behaviours to school entry 19 , 20 . An Australian prospective cohort study following children to adulthood reported screening children at 5 years of age for behavioural, social and emotional concerns poorly predicted psychopathology at 21 years of age 21 .…”
Section: Discussionmentioning
confidence: 99%